The Role Of The Regional House Of Representatives And Local Government In The Process Of Formulating Local Regulations In The City Of Bengkulu - Syahputera, Ryan Pratama; Saputra , Harius Eko; Handayani , Tuti (Utami Publisher, 2025)
This study aims to determine the role of the Regional Representative Council (DPRD) in the process of drafting regional regulations in Bengkulu City. The method used in this study is descriptive qualitative. There are four (4) informants in this study, consisting of two (2) key informants and two (2) main informants. The data collection methods used are observation, interviews, and documentation. Based on the results of the research and discussion using Soerjono Soekanto's Role Theory (2013:243): (1) The role of the DPRD in the drafting of regional regulations on the formation and structure of regional apparatus: discussing and approving drafts submitted by regional heads, conducting material tests on draft regional regulations to ensure their suitability with regional needs and national regulations. (2) The role of the regional government in drafting regional regulations on the structure of regional apparatus: drafting regional regulations based on technical studies and regional needs, referring to the guidelines set out in Government Regulation No. 18 of 2016, coordinating with the DPRD during the discussion of the draft regional regulation, involving community organizations, academics, and experts to draft participatory regional regulations.